Análise das tensões de água no solo cultivado com morangueiro sob poda - Teixeira, Rafael Pombo [UNESP]; Pereira, Geraldo Magela; de Souza, Rovilson José; Garcia, Henrique Hudari; da Gama, Gustavo Bosco Nogueira (My University, 2013)
Strawberry yield and quality was evaluated after drastic pruning (second cycle), under different soil water tensions, drip irrigation. The experiment was conducted on beds at a greenhouse, located at Engineering Department, Federal University of Lavras (UFLA), from April to December of 2010. An experimental design was in randomized blocks with three replicates. The treatments were composed of six different soil water tension, 15, 25, 35, 45, 55 e 70 kPa. Results obtained allowed to verify that to higher values of: total and commercial fresh weight of fruits per plant, total and commercial number fruits per plant and total and commercial yield, it is necessary to irrigate when soil water tension gets approximately to 15 kPa, at 0.15 m deep. Commercial average fruit mass and noncommercial fresh weight of fruits per plant, were not reduced under different soil water tensions applied.

Objetivou-se com este estudo avaliar o efeito de diferentes tensões de água no solo cultivado com morangueiro após poda drástica (segundo ciclo), irrigado por gotejamento. O experimento foi conduzido em canteiros no interior de uma casa de vegetação, localizada na área experimental do Departamento de Engenharia da Universidade Federal de Lavras (UFLA), no período de abril a dezembro de 2010. O delineamento experimental utilizado foi em blocos casualizados (DBC), com três repetições. Os tratamentos constituíram-se de seis tensões de água no solo, 15, 25, 35, 45, 55 e 70 kPa. Concluiu-se que, para a obtenção dos maiores valores de massa fresca de frutos totais e comerciais por planta, número de frutos totais e comerciais por planta e produtividade total e comercial, deve-se irrigar no momento em que a tensão de água no solo estiver em torno de 15 kPa, à profundidade de 0,15 m. A massa média de frutos comerciais e a massa fresca de frutos não comerciais por planta não foram afetadas pelas distintas tensões de água no solo.
Water tension analysis in soil grown with strawberry under pruning
Keywords: Drip irrigation; Irrigation management; Pruning strawberry; drip irrigation; experimental study; irrigation system; soil water; tension; water management; water supply